Sustainable ballistic solutions for recycling silkworm cocoon waste into high-performance bulletproof materials - Sutha Loidueanchai; Varinrumpai Seithtanabutara; Apichart Artnaseaw (Green Chemistry Letters and Reviews)
This study aims to develop a method for producing ballistic panels meeting NIJ Level IIIA standards by integrating silkworm cocoon waste (SCW) as reinforcement and utilizing bias fabric through cold pressing. Various SCW quantities (100 g designated as P2, 150 g designated as P3, and 225 g designated as P4) alongside 50 g of resin and 230 g of bias fabric were used, comparing six (type I) and three (type II) layer patterns. Panels with SCW exhibit enhanced mechanical properties, particularly in type II layouts, which show superior performance in tensile, impact, and flexural resistance. Ballistic impact tests reveal that only type I-P3, I-P4, II-P3, and II-P4 composite panels effectively stop bullet penetration, with BFS measurements ranging from 10.6–14.6 mm, below the 44 mm NIJ standard limit. Consequently, the study indicates that II-P3 is selected for producing bulletproof armor compliant with NIJ Level IIIA standards, supported by the method's simplicity, cost-effectiveness, and consistent outcomes. The decision to use II-P3 for producing ballistic panels is made due to its simplified processing requirements. Upon calculating the total component cost for panels sized at 150 × 150 mm, it is established that each panel has a cost of $1.5.